Seismic assessment and strengthening of an existing steel bridge in Portugal - Fernandes, C. (2012)
This article presents the seismic vulnerability assessment of the S. João de Loure bridge, in Portugal. The single span steel bridge has riveted joints, commonly affected by corrosion, which can lead to a significant stiffness reduction. With the objective of evaluating the influence of the joints stiffness in the structural response of the bridge, a structural model of the bridge was created, and natural frequencies, maximum axial forces and maximum stresses, and maximum mid-span deflection were analysed. Four possible element rupture scenarios where also studied. Two of them where proved to be a risk for the structural safety of the bridge. A commonly used strengthening solution intending to reduce the bridge’s mid-span deflection with external pre-stressing cables was studied.